Analysis of Public Policy of The Ministry of Law and Human Rights of West Kalimantan in Encouraging Trademark Registration - Husyam Husyam; Supardi Supardi; Zakiyul Faqih (Rechtsvinding, 2026)
Trademark registration plays a crucial role in protecting businesses and helping to create healthy and fair businesses. Through public policy, the government is responsible for ensuring that trademark protection is accessible and utilized by the public, particularly businesses. This article examines how policies implemented by the Ministry of Law, specifically the West Kalimantan Regional Office of the Ministry of Law, encourage businesses to register their trademarks as a form of legal protection and to strengthen the regional economy. This research uses a qualitative approach with public policy analysis and legal effectiveness theory to determine whether existing policies are running according to their objectives and meet real-world conditions. The study results indicate that the West Kalimantan Ministry of Law and Human Rights has undertaken various efforts, such as outreach, mentoring, and facilitation of trademark registration in accordance with Law Number 20 of 2016 concerning Trademarks and Geographical Indications. These efforts have been quite effective for businesses directly involved in government programs, particularly fostered MSMEs. However, this policy has not been widely recognized due to low legal awareness, economic constraints, and the public's perception that trademark registration is not yet a necessary necessity. Therefore, a strengthened state role, more integrated policies, and cross-sectoral collaboration are needed to ensure a more effective and sustainable trademark registration policy.